Emotional Intelligence and Job Satisfaction: The Mediating Role of Work-Life Balance Among IT Professionals in Uttar Pradesh - Ali, Anamta; Orooj Siddiqui (International Journal of Computational and Experimental Science and Engineering, 2025)
The present investigation examines the multifaceted linkage, investigating how emotional intelligence (EI) influences levels of job satisfaction (JS) within the of cohort of IT professionals operating in the state of Uttar Pradesh, with a specific focus on exploring how equilibrium between professional and personal domains serves as a conduit for indirect effects. In the rapidly evolving IT sector, understanding how psychological factors like EI contribute to employee satisfaction constitutes a critical determinant in optimizing organizational efficacy and fostering holistic employee well-being.Employing a structured quantitative methodology, empirical data were systematically gathered from 552 respondents across five major IT hubs in Uttar Pradesh through a structured questionnaire. Quota sampling ensured proportional representation across technical, managerial, and other professional roles. Mediation effects were examined utilizing Hayes’ PROCESS Macro (specifically Model 4) to examine direct, indirect, and total effects.The results reveal that emotional intelligence significantly manifests job satisfaction both as a direct effect and as an indirect pathway mediated through the facilitation of work-life balance (WLB). The mediation analysis substantiates that WLB functions as a critical intermediary, amplifying the association between EI and JS. Empirical evidence indicates that individuals exhibiting elevated levels of EI are more likely to attain an enhanced equilibrium between professional and personal domains, which consequently fosters greater job satisfaction.These results emphasize the strategic value of embedding emotional intelligence enhancement and WLB frameworks within organizational policies to optimize employee well-being and productivity. These insights can guide HR professionals and managers in designing targeted interventions enhance organizational commitment and mitigate occupational exhaustion, and foster a more resilient workforce